2013
DOI: 10.1186/1471-2474-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral pre-solidified chitosan/blood implants elicit reproducible early osteochondral wound-repair responses including neutrophil and stromal cell chemotaxis, bone resorption and repair, enhanced repair tissue integration and delayed matrix deposition

Abstract: BackgroundIn this study we evaluated a novel approach to guide the bone marrow-driven articular cartilage repair response in skeletally aged rabbits. We hypothesized that dispersed chitosan particles implanted close to the bone marrow degrade in situ in a molecular mass-dependent manner, and attract more stromal cells to the site in aged rabbits compared to the blood clot in untreated controls.MethodsThree microdrill hole defects, 1.4 mm diameter and 2 mm deep, were created in both knee trochlea of 30 month-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
1
36
2
Order By: Relevance
“…6,19 The sulfated glycosaminoglycan (GAG) content of engineered tissues was quantified by ELISA using dimethylmethylene blue (DMMB; Sigma Aldrich) colorimetric assay with chondroitin sulfate from shark cartilage to generate a standard curve. Total DNA content was measured using Quit-iT dsDNA kit (Invitrogen) with salmon test DNA to generate a standard curve.…”
Section: Biochemical Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…6,19 The sulfated glycosaminoglycan (GAG) content of engineered tissues was quantified by ELISA using dimethylmethylene blue (DMMB; Sigma Aldrich) colorimetric assay with chondroitin sulfate from shark cartilage to generate a standard curve. Total DNA content was measured using Quit-iT dsDNA kit (Invitrogen) with salmon test DNA to generate a standard curve.…”
Section: Biochemical Measurementmentioning
confidence: 99%
“…6,20,21 In brief, bone marrow was aspirated from the posterior superior iliac crest, and mononuclear cells (MNCs) were isolated by density gradient centrifugation. Cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Gibco) supplemented with 10% fetal bovine serum (FBS; Gibco), 1% HEPES buffer, and 1% antibiotics-antimycotics in a 37°C, 5% CO 2 incubator.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other laboratories have attempted to augment the interfacial mechanical properties of engineered cartilage and subchondral bone using biomaterials such as chitosan particles [48], porous calcium polyphosphate [49], chitosan-chondroitin sulfate [50]. One group even used HA in conjunction with non-photopolymerizable alginate hydrogels and reported on its shear mechanical properties [18,51].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Hoemann et al [17] indicated that Chitosan glycerol phosphate when mixed with blood in the cartilage defect space not only formed greatly improved integration with sub-chondral bone, but also resulted in enhanced hyaline cartilage tissue formation. Indeed, in vivo (primarily in the rabbit model) cartilage tissue engineering studies have shown convincing bone marrow stem cell migratory responses towards the ostechondral interface and subsequent tissue remodeling when chitosan was utilized [47,48].…”
Section: Discussionmentioning
confidence: 99%